สภาร่างรัฐธรรมนูญกับการร่างรัฐธรรมนูญตามแนวรัฐธรรมนูญนิยม - วลัยมาศ แก้วศรชัย (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
In many democratic States, the Constitutionalism is a fundamental concept for drafting and interpreting the Constitution so as to secure rights and liberties of individuals from an abuse of power. The Constitution of those States are therefore systematic, effective, and justifiable because, under Constitutionalism concept, the relationships between the State, people and political organizations are imposed with regards to rights and liberties of individuals and functions of the States. In Thailand, however, it appears from the result of the research that even though Thailand, along the past 60 years, had 15 Constitutions, but many problems in Thai political system are standstill. This is because those Constitutions had been drafted without regards to problems of the Thai political in all aspects. It could therefore be said that the Constitutionalism never been established completely in Thailand. It is nevertheless noticeable that the new Constitution drafted by the "Constitution Drafting Assembly," the special organization established to drafting of the new Constitution under the Constitution of the Kingdom of Thailand as amended by the Constitution of the Kingdom of Thailand (No.6), B.E. 2539 is quite different from the past Constitutions in essence, especially in rules and for making the draft Constitution. The Constitution Drafting Assembly firstly did collect all problems of Thai political system and, then, analyst the measure to overcome those problems systematically. This is te reason why an essence of the draft Constitution which had been proclaimed to be the Constitution of the Kingdom of Thailand, B.E. 2540 in 1997 comply with the Constitutionalism concept more than its forerunners. It could therefore be said that the Constitutionalism concept is established firstly in Thailand in the Constitution of the Kingdom of Thailand, B.E. 2540 and rights liberties of individuals shall be effectively and completely secured as that of people in any other democratic countries since then.